2018
DOI: 10.1038/s41598-018-35046-7
|View full text |Cite
|
Sign up to set email alerts
|

Bayes-Like Integration of a New Sensory Skill with Vision

Abstract: Humans are effective at dealing with noisy, probabilistic information in familiar settings. One hallmark of this is Bayesian Cue Combination: combining multiple noisy estimates to increase precision beyond the best single estimate, taking into account their reliabilities. Here we show that adults also combine a novel audio cue to distance, akin to human echolocation, with a visual cue. Following two hours of training, subjects were more precise given both cues together versus the best single cue. This persiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 48 publications
3
42
1
Order By: Relevance
“…Examples of such experiences can be infrared (IR) vision conveyed through sound or ultrasound perception through touch. Initial evidence confirms that NSEs can be induced in humans via SSDs (Kaspar et al, 2014;König et al, 2016;Negen et al, 2018).…”
Section: Does the Concept Of Reversible Plasticity Gradient Extend Almentioning
confidence: 76%
“…Examples of such experiences can be infrared (IR) vision conveyed through sound or ultrasound perception through touch. Initial evidence confirms that NSEs can be induced in humans via SSDs (Kaspar et al, 2014;König et al, 2016;Negen et al, 2018).…”
Section: Does the Concept Of Reversible Plasticity Gradient Extend Almentioning
confidence: 76%
“…A recent study with adults also fits with this type of explanation (Negen, Wen, Thaler, & Nardini, 2018). Adults were asked to learn new depth cues -based either on sound delay or wrist vibration -and combine these with a noisy visual cue.…”
Section: The Hard Limit At 10-11 Hypothesismentioning
confidence: 85%
“…Indeed, a recent tutorial detailing how to test for optimal cue integration has proposed a visual taxonomy by which one can judge the fit of a set of data to MWF by visual inspection of the data, associated error bars and model predictions (Rohde et al, 2016). This taxonomy has started to be used researchers to assess the adherence to MWF (Negen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent review has suggested that the adherence to optimal cue integration (without comparison to alternative models) can be assessed visually and has provided a visual taxonomy of "optimal", "sub-optimal", "ambiguous", "near optimal" and "supra-optimal" performance (Rohde et al, 2016, p. 23). This visual taxonomy, of judging the fit to the predictions of optimal cue integration based upon visual inspection of (1) the data, (2) the error bars around the data, and (3) the predictions of optimal cue integration, has started to be used by researchers to assess "optimality" of experimental data through adherence to MWF (Negen, Wen, Thaler, & Nardini, 2018).…”
Section: Alternative Models To Mwfmentioning
confidence: 99%